Studies in Rabbinic Hebrew - Heijmans, Shai (Cambridge Semitic Languages and Cultures Series, 2020)
"This volume presents a collection of articles centring on the language of the Mishnah and the Talmud - the most important Jewish texts (after the Bible), which were compiled in Palestine and Babylonia in the latter centuries of Late Antiquity. Despite the fact that Rabbinic Hebrew has been the subject of growing academic interest across the past century, very little scholarship has been written on it in English. Studies in Rabbinic Hebrew addresses this lacuna, with eight lucid but technically rigorous articles written in English by a range of experienced scholars, focusing on various aspects of Rabbinic Hebrew: its phonology, morphology, syntax, pragmatics and lexicon. This volume is essential reading for students and scholars of Rabbinic studies alike, and constitutes the second in a new series, Studies in Semitic Languages and Cultures, in collaboration with the Faculty of Asian and Middle Eastern Studies at the University of Cambridge. "